Measuring the increasing connectedness of Chinese assets with global assets: using a variance decompositions method. (14th February 2019) - Yu, Honghai; Sun, Wencong; Ye, Xiangting; Fang, Libing
Abstract: This study uses the network topology of variance decompositions to investigate the connectedness of four assets (stocks, bonds, foreign exchange and commodities) across five countries (US, EU, UK, Japan and China). We find that connectedness to and from the Chinese asset markets increased significantly from 2013 to 2018, which reveals that Chinese assets have gradually become integrated into the global economy. We also investigate the volatility connectedness in economically fragile periods and find that the Chinese market acted as a transmitter of volatility in the 2015 Chinese stock crash. This finding is potentially essential to modern risk measurement and management.